The bang for the birr: Public expenditures and rural welfare in Ethiopia - Mogues, Tewodaj; Ayele, Gezahegn; Paulos, Zelekawork (International Food Policy Research Institute, 2007)
This paper explores and compares the impact of different types of public spending on rural household welfare in Ethiopia. The analysis of public financial and household-level data reveals that returns to road investments are significantly higher than returns to other spending, but are much more variable across regions. This regional variability in returns to road investment suggests that the government should carefully consider region-differentiated investment priorities. Some evidence suggests that the returns to road spending are increasing over time, with higher returns to road investments seen in areas with better-developed road networks. Among the other types of public spending, the household expenditure impacts of per capita public expenditure in agriculture and education are smaller, but these effects are also less variable across regions than the effects of road infrastructure spending. The largest effects of agricultural expenditures on rural households are observed in the most urbanized regions, pointing to the potentially important impact of market proximity on returns to public interventions in agriculture. Despite the importance of agriculture to the economy of Ethiopia we found that returns to agricultural spending were fairly low, suggesting the need for further research into the drivers of efficiency and effectiveness of public investments in this important sector.